(untitled) - Burrage, Thomas F. (Hoboken, N.J., 2003)
Divorce and Domestic Relations Litigation represents the accountant's body of knowledge on divorce and domestic relations and how it relates to the divorce process, alimony, child support, and property. At once a reference tool and a training guide for firms entering this specialization, this book provides the financial professional with a single source of information regarding the financial impact, the practical course, and the underlying theories that impact domestic relations
Keywords: Divorce,Matrimonial actions,Divorce,Trung tâm Học liệu ĐHCT; Law and legislation,Economic aspects,Thủ tục ly hôn; United States,United States,United States,Hoa Kỳ